EFFECT OF SUBCUTANEOUS RECOMBINANT HUMAN ERYTHROPOIETIN ON BLOOD PRESSURE IN PRE-DIALYSIS CHRONIC KIDNEY DISEASE (CKD) PATIENTS - Muhammad Sajid Hussain (Army Medical College Rawalpindi, 2021)
Objective: To determine the effect of subcutaneous recombinant human erythropoietin on blood pressure in pre-dialysis chronic kidney disease (CKD) patients. Study Design: Case-series descriptive study. Place and Duration of Study: Combined Military Hospital Peshawar, from Mar 2016 to Sep 2016. Methodology: A total of 100 cases were enrolled. Inclusion criteria was patients of 18 to 60 years of both gender & estimated glomerular filtration rate (eGFR) below 30 mL/min/1.73 m2 having Hb <10g/dL and pre-dialysis while Exclusion Criteria was pregnancy or lactation, BP more than 140/90 mmHg, patients on Haemodialysis and worsening renal function. Baseline BP, body weight and eGFR of anaemic chronic kidney disease patients were recorded prior to EPO Alpha therapy. Erythropoiesis-stimulating agents (ESAs) i.e. EPO Alpha (50-100 Units/kg thrice or once weekly) was administered subcutaneously. Subsequent blood pressure, body weight and eGFR monitoring was done after 2 and 4 weeks post EPO Alpha injection. Results: Mean age range was 46.71 years with range of 20-60 years, 73 (73%) were male while 27 (27%) were females. Mean ± SD for other quantitative variables like eGFR was 23.12 ± 5.28, Hb levels (g/dL) was 8.62 ± 0.85, Weight (kg) was 56.66 ± 6.62 and duration of CKD was 9.87 ± 4.02. Frequency of Hypertension (post EPO) was 2 (2%) and p-value was 0.453. Conclusion: We concluded that the frequency of hypertension in pre-dialysis patients with chronic kidney disease (CKD) receiving recombinant human erythropoietin (rhEPo) subcutaneously (SC) in low doses, is very low, so rhEPo can be used subcutaneously for treatment of anemia in pre-dialysis CKD patients